Use of HLA-B*58:01 genotyping to prevent allopurinol induced severe cutaneous adverse reactions in Taiwan: national prospective cohort study. (23rd September 2015) - Ko, Tai-Ming; Tsai, Chang-Youh; Chen, Shih-Yang; Chen, Kuo-Shu; Yu, Kuang-Hui; Chu, Chih-Sheng; Huang, Chung-Ming; Wang, Chrong-Reen; Weng, Chia-Tse; Yu, Chia-Li; Hsieh, Song-Chou; Tsai, Jer-Chia; et al.
Abstract : Objective To evaluate the use of prospective screening for the HLA-B*58:01 allele to identify Taiwanese individuals at risk of severe cutaneous adverse reactions (SCARs) induced by allopurinol treatment. Design National prospective cohort study. Setting 15 medical centres in different regions of Taiwan, from July 2009 to August 2014. Participants 2926 people who had an indication for allopurinol treatment but had not taken allopurinol previously. Participants were excluded if they had undergone a bone marrow transplant, were not of Han Chinese descent, and had a history of allopurinol induced hypersensitivity. DNA purified from 2910 participants' peripheral blood was used to assess the presence of HLA-B*58:01. Main outcome measures Incidence of allopurinol induced SCARs with and without screening. Results Participants who tested positive for HLA-B*58:01 (19.6%, n=571) were advised to avoid allopurinol, and were referred to an alternate drug treatment or advised to continue with their prestudy treatment. Participants who tested negative (80.4%, n=2339) were given allopurinol. Participants were interviewed once a week for two months to monitor symptoms. The historical incidence of allopurinol induced SCARs, estimated by the National Health Insurance research database of Taiwan, was used for comparison. Mild, transient rash without blisters developed in 97 (3%) participants during follow-up. None of the participants was admitted to hospital owing to adverse drug reactions. SCARs did not develop in any of the participants receiving allopurinol who screened negative for HLA-B*58:01. By contrast, seven cases of SCARs were expected, based on the estimated historical incidence of allopurinol induced SCARs nationwide (0.30% per year, 95% confidence interval 0.28% to 0.31%; P=0.0026; two side one sample binomial test). Conclusions Prospective screening of the HLA-B*58:01 allele, coupled with an alternative drug treatment for carriers, significantly decreased the incidence of allopurinol induced SCARs in Taiwanese medical centres.